Continuous Self‐Healing Life Cycle in Vascularized Structural Composites. (14th April 2014) - Patrick, Jason F.; Hart, Kevin R.; Krull, Brett P.; Diesendruck, Charles E.; Moore, Jeffrey S.; White, Scott R.; Sottos, Nancy R.
<x xml:space="preserve">Abstract</x> By incorporating 3D microvascular networks containing a two‐part reactive chemistry within a fiber‐reinforced composite, continuous cycles of self‐healing after interlaminar delamination are achieved. An interpenetrating vasculature shows improved in situ fluid mixing over segregated microchannels, resulting in full recovery (>100%) of mode‐I fracture resistance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>